Rod-shaped barium sulfate particles from a completely inorganic system - Radomirovic, Tomoko; Ogden, Mark; Jones, Franca (Elsevier Science BV, 2011)
Rod-shaped barium sulfate particles can be formed from purely inorganic systems at 75 1C and theseparticles are single crystals elongated in the c-axis. This c-axis growth promotion relative to the othercrystal faces is absent when the cation impurities are absent suggesting a specific interaction of thecations with the growing crystal. Attempts have been made to determine the cause of this c-axisgrowth promotion, but no one mechanism appears to adequately explain this effect and it may be dueto a combination of different impacts. The same cations do not induce rod-shaped particles at 25 1C,thus suggesting an important role of kinetics in the crystallization of these particles. Finally, previousreports suggesting that the formation of rod-like particles is due to the presence of an organic additivemay be incorrect as sufficient sodium ions may have been present to give these particles even in their absence.